Implementation of Electricity Supply According To Law No. 30 of 2009 Concerning Electricity In Prospective Public Services - Awaluddin Awaluddin; Basri Mulyani; ABD Muhid (Journal of Law, Politic and Humanities, 2026)
This study aims to analyze the implementation of electricity supply based on Law Number 30 of 2009 concerning Electricity from a public service perspective at PT PLN (Persero) ULP Selong, East Lombok Regency. The study uses an empirical legal method with an empirical juridical approach through observation, interviews, documentation, and literature studies. The results of the study indicate that the implementation of electricity services has implemented the principles of public service in the form of professionalism, transparency, accountability, legal certainty, and the use of digital technology through the PLN Mobile application. Service constraints are still influenced by geographical conditions and natural factors. The study concludes that the implementation of Law Number 30 of 2009 has gone well, but improvements in infrastructure quality, disruption mitigation, and equal distribution of services are still needed to realize optimal public services